PENGARUH REMUNERASI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA PEGAWAI DI KANTOR PERTANAHAN KABUPATEN BADUNG - Kadek Ayu Putri Dwiyanti; I Ketut Yudana Adi; Made Christin Dwitrayani (Universitas Triatma Mulya, 2021)
Badung National Land Agency is a government agency that has the task of carrying out affairs in the field of land and spatial planning. With this responsibility, the government provides remuneration as one of the ways to improve employee performance and of course with a good internal control to achieve the goals set. This study aims to determine the effect of remuneration and internal control systems on employee performance at the Badung National Land Agency. Data was obtained by distributing questionnaires to civil servant with certain criteria at the Badung National Land Agency. The results of this study indicate that there is a simultaneous influence on the variable remuneration and internal control system on employee performance, it can be seen that the F count value is 39.055> F table is 2.72 with a significance level of 0.000 <0.05. The results of this study also showed that the t-count value of the remuneration variable was (3,801), the internal control system (2,487) was greater than the table (1,669), so it was stated that there was an influence on employee performance. In the determination test, there is an effect of 49.9% of the independent variables (remuneration and internal control systems) on the dependent variable (employee performance). Meanwhile, as much as 50.1% is influenced by other variables and is not included in this regression analysis, such as work culture, work motivation, competence, and accounting informationsystems.